Nocturnal hormonal responses to resistance exercise - McMurray, R. G.; Eubank, T. K.; Hackney, A. C. (European Journal of Applied Physiology, 1995)
The effects of resistance exercise on the nocturnal responses of cortisol (CO), testosterone (TEST), human growth hormone (hGH), and thyroid hormones (T3, T4) were examined in eight trained weight lifters. Each subject completed two trials using a counterbalanced design: a control, no exercise trial (CON) and a heavy resistance exercise session of three sets of six exercises to exhaustion (RE). The exercise session took place between 1900 and 2000 hours. Blood was sampled prior to and at 20-min intervals after RE. For both trials blood was sampled at hourly intervals from 2100 hours until 0700 hours. The hGH and CO concentrations were increased up to 40-min post-exercise (P < 0.05), but returned to resting levels 1 h post-exercise. Nocturnal hGH concentration was not affected by RE (P > 0.26) and peaked at 0200 hours and declined until 0700 hours. Similarly, the CO responses were similar between the trails (P > 0.14). This CO concentrations declined from 2200 hours until 0100 hours, then increased steadily until 0700 hours. The TEST concentrations during both trials rose steadily from 2200 hours until 0700 hours; however, the rise in TEST from 0500-0700 hours during RE was greater than during the CON trails (P = 0.059). The T3 concentrations were unchanged by exercise and were similar at all times between trails. The T4 concentrations were elevated for 20 min after RE; however nocturnal T4 concentrations were lower after RE than during CON. These results would suggest that hGH and CO may have limited nocturnal reactivity to resistance exercise. However, the nocturnal alterations of TEST and T4 after resistance exercise, although small, may have implications for muscle anabolism.